Photoacoustic detection of d-d transitions and electronic structure of three polyamine copper complexes - Guskos, N.; Papadopoulos, G.; V. Likodimos; Mair, G.L.R.; Majszczyk, J.; Typek, J.; Wabia, M.; Grech, E.; Dziembowska, T.; Perkowska, T.A. (Journal of Physics D: Applied Physics, 2000)
The potential of photoacoustic spectroscopy to resolve the crystal field levels of Cu2+ ions in three polyamine copper complexes, aqua spermine copper sulfate trihydrate [NH2(CH2)3NH(CH2)4NH(CH2)3 NH2·Cu2+·H2O]·SO42-·3H2O, norspermine copper sulfate trihydrate [NH2(CH2)3NH(CH2)3NH(CH2)3 NH2·Cu2+·SO42-]·3H2O, and homospermine copper sulfate dihydrate [NH2(CH2)3 NH(CH2)2NH(CH2)3 NH2·Cu2+·SO42-]·2H2O, has been explored along with UV/VIS and electron paramagnetic resonance (EPR) spectroscopy. Intense absorption is detected in the photoacoustic spectrum corresponding to the d-d transition band weakly traced in the corresponding optical spectrum. The observed fine structure photoacoustic lines are assigned to the individual d-d transitions of Cu2+ ions, which are further exploited to determine the diverse metal-ligand interaction of the studied compound employing simple crystal field analysis.
cited By 13